2000
DOI: 10.1093/oxfordjournals.schbul.a033468
|View full text |Cite
|
Sign up to set email alerts
|

Is Anhedonia a Specific Dimension in Chronic Schizophrenia?

Abstract: This article explores the relationships among anhedonia, depression, and schizophrenic symptomatology in chronic schizophrenia. To explore these relationships, factor analysis methods were used to analyze the latent organization of the variables. The Fawcett Clark Pleasure Capacity Scale-Physical Pleasure (FCPCS-PP) and the abridged version of the Beck Depression Inventory (BDI) were completed by 150 subjects who met research diagnostic criteria for definite chronic schizophrenia. The schizophrenic symptomatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 55 publications
(82 reference statements)
4
13
0
Order By: Relevance
“…This finding strongly corroborates the work of Loas et al (1996Loas et al ( , 2000 who found anhedonia as a construct that is distinct from both, depression and negative symptoms in chronic schizophrenia. According to Andreasen (2000), 'identifying the correct phenotype of schizophrenia is perhaps the most important goal of modern research in schizophrenia'.…”
Section: Discussionsupporting
confidence: 90%
“…This finding strongly corroborates the work of Loas et al (1996Loas et al ( , 2000 who found anhedonia as a construct that is distinct from both, depression and negative symptoms in chronic schizophrenia. According to Andreasen (2000), 'identifying the correct phenotype of schizophrenia is perhaps the most important goal of modern research in schizophrenia'.…”
Section: Discussionsupporting
confidence: 90%
“…This finding confirms previous results in the literature that found anhedonia to be independent from negative symptoms 26,74,[76][77][78][79] and could reflect the ability of these scales (i.e.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…A high level of anhedonia could be related to depression, which constitutes a strong predictor of suicide in schizophrenic subjects [1] , but using the same cohort we reported that physical anhedonia was independent of the negative and depressive dimensions of schizophrenia [15] . To explain these discordant findings it is useful to take into account the heterogeneity of anhedonia.…”
Section: Discussionmentioning
confidence: 74%
“…The patients gave informed consent to the study after it had been explained. Initially, the cohort had been created to explore anhedonia in chronic schizophrenia [15] .…”
Section: Subjectsmentioning
confidence: 99%